MENINGKATKAN KEMAMPUAN TEKNIK LOMPAT JAUH GAYA JONGKOK DENGAN MENGGUNAKAN ALAT BANTU TALI RINTANGAN DI KELAS VII-3 SMP NEGERI VII-3 SMP NEGERI 1 PATUMBAK TAHUN PELAJARAN 2018/2019 - Daslan Gultom (ANSIRU PAI : Pengembangan Profesi Guru Pendidikan Agama Islam, 2020)
Long jump skills are one of the athletic branches that must be given to students of class VII-3 SMP Negeri 1 Patumbak. The ability of students' cognitive factors in understanding movement techniques that must be done in long jump really contributes to the achievement of optimal jump results. The long jump skills of Class VII-3 students of SMP Negeri 1 Patumbak are very low, this situation is very far from the author's expectation as a sports teacher by looking at the long jump participants' score on the Porseni which is 460 cm, this makes the author interested in conducting research through research. Classroom Action (CAR) with the title "Improving the Ability of the Squat Style Long Jump Technique by Using Obstacle Rope Tools in class VII-3 SMP Negeri 1 Patumbak". Based on the function of physical education, to achieve the expected goals, one of the efforts that can be made is the delivery of learning that is effective and in accordance with the characteristics of junior high school students. The method used in this research is classroom action research which consists of two cycles in height and each cycle consists of one learning action. The object of this research is the students of Class VII-3 SMP Negeri 1 Patumbak. The time of the research was carried out in the odd semester of the 2018/2019 academic year. The conclusions in this research are: (1) at sik us 1 the data obtained from the long jump squatting force an average of 290 cm and in cycle 2 an average of 314 cm, (2) there is an increase in learning outcomes squat style long jump using rope aids hurdle.